Licia’s Lectures on Nothing - Moten, Fred (Current Musicology, 2018)
When nothing is left on Earth to feel the warmth of the sun When no one is left on Earth to invoke God When not even pain will be felt on earth There will only be a flame and that flame will be love, Love, love! To begin again. Considering its lugubrious content, it seems odd, more than forty years later, that the music industry and listening public frantically celebrated “nothingness” in this very melodramatic way. The muscular symphonic orchestra rushed to keep pace with the singer who had appeared, seemingly out of nowhere and literally came out of the nowhere that was Puerto Rico to Latin America, the United States, and the world. Licia Fiol-Matta, The Great Woman Singer, 1 And God said let there be a little light: and there was this little light of nonbelonging, Lucecita and her “Génesis.” Her light is given brightest in an incoherence she bears. It’s not that Lucecita can’t but that no one can be the voice of the nation. Having already shown how the nation can’t have a mother, Licia Fiol-Matta shows us that the nation can’t have a voice, either. Women, in being continually enjoined to do the impossible, are irreducible to that imposition, which is why and how they carry the extranational flavor and desire of the nation’s refusal, its nonperformance. Licia allows us to hear Lucecita’s perfectly deviant moral perfectionism (the truth; the objective account of the good life which is, eventually, crystallized into a sense of the absolute necessity of freedom): I have only one weakness / which I share with all my might / I must be free. I want to be perfect. I am not pro-independence, I am not a nationalist, I am nothing. The only thing you can’t allow is to have your freedom taken from you because then you become nothing. I must be free. I desire freedom. I want to enjoy freedom. I have a taste for liberty. I can taste it. I can feel it in my mouth. Freedom is very sweet. The mouthfeel of freedom. Evangelical perfectionism, neither identification nor plenitude, but truth in transport, suspension, via signal not symbol, having refused the readily legible. There is a discourse on nothing, on nothingness and nowhere, with which Licia begins. Is the lyrical content of “Génesis” really lugubrious? What about that little drum figure, that husky-voiced intro to a bombast of strings and woodwinds? Isn’t it the music and not the words that threaten too sweetly to overwhelm. What would it be for nothing to be left on earth? This pop-zen attitude hit the English-speaking world a couple of years later with John Lennon’s “Imagine,” also echoing a convergence that had already occurred in Don Cherry’s 1970 Mu, re-echoed a few years later in Billy Preston’s “Nothing from Nothing.” But “the nowhere that is Puerto Rico” is where it all begins, remaining special, as it were, in the manmade persistence of the storm. What is the nature of this sub-national, anti- and ante-national, international nowhere? If we consider the residual insurgency of the historical irrelevents, as Zbigniew Brzenski calls them, which Greil Marus famously recites in his history of punk music, Lipstrick Traces, then Lucecita is a punk artist, as much as The Slits, in being more + less than a “great woman singer.” More precisely, she exemplifies that proto-punk thing that constituted the insurgency that punk came along to mourn in its recrudescent whiteness. This is almost like the historical transition and loss of the lower east side, which will have already occurred by the mid-seventies, if you’ll forgive that weird sleight of hand with tense and case, a subjunctivity already buried. What was the mood of the times? The loss will have occurred long ago. If it occurs, the loss will have occurred long ago. The absolute nothing of dissolution, of ceasing to be, which “Génesis” evoked, gave way to the relative nothing that the singer claimed for herself, when she informed the public that it could not dictate what she was. “I am nothing,” she said in 1974, furiously and presciently. She was not legibility, but potentiality. She could not be generalized. She was singular. That’s what she meant when she said, “I am nothing” (3). She pits a supposedly general anxiety regarding nuclear apocalypse against a singular assertion of a non-generalizable self. But what if Lucecita’s position in all this is the other way around—a refusal of geo-politics that is also a refusal of self? In this regard, being nothing is more + less than singular. It undermines that math, that structure of accounting, its spatio-temporal constitution. And this will have moved by way of the specific gender-non-conformity of a richly internally differentiated, Puerto Rican anti-colonial and internationalist anti-nationalism. Can there be a shared anti-nationalism that mobilizes certain features of nationalism on its behalf? What would the dangers of such expediency be? If the nation has a queer mother is it stillborn or, deeper still, mutant? Must it have certain developmental delays or disorders? Perhaps it’s disorder will have been total, in a Fanonian sense. And this disorder must be thought with greater intensity in the wake of unnatural disaster. What if the thing people think they want to call decolonization is an effect, finally, of these subnational ensembles and (non)performances, these errant underdevelopments that emerge when the anti- and ante-nation is handed, as Spillers might say, by the mother? Of course, the normative discourse of nationhood is deeply committed to a certain fixation on and of the mother, her necessity troubled by a vulnerability she constitutes in being-constitutive. But here, the nation is disfigured by a kind of patriarchal absence or eclipse even within the general atmosphere of the settler’s patriarchal order. It’s like Lucecita is the dissident star of the Moynihan report, her diminutive female masculinity constantly subject to a diminution she won’t take, an infantilization her deviant function will have actively failed to bear. It’s like Las Nietas de Nonó literally obliterates the mathematics of a single subject’s relation to nation and the boundaries that structure what it is or is not to be a singer. The iconic figure of the nation, of national womanhood, just won’t work out. What if the first move of decolonization is to accept this monstrosity, this disfiguration? This is a modified Arturo Escobar/Manfred Max-Neef kinda question regarding the necessity of the embrace of and the continual differentiation and cultivation of underdevelopment, something which the current intensification of disaster, which is a disaster of development, not underdevelopment, itself only further intensifies. It makes you want to consider, again, national moral perfectionism and the future (im)perfect—an action that will have been completed at some point toward which we incompletely tend with errant precision. Puerto Rico will have developed, or will have been developed by, when? What if the end of the world that Lucecita finds in the song is not so much marked by extinction but by the refusal of development, of a certain national perfection? Perhaps the imperfect future of or in the voice coincides with that which hasn’t happened yet. Lucecita would bear this—even as she shows that kind of singularist moral perfectionism that Licia shows—as something not quite bearable. What if self is not only in defiance of the nation but also its secret sharer, its accursed share, its irreducibly necessary instrument, element and remainder? “Nada,” as Licia teaches us, is also “that’s it,” or that’s all, or that’s the end—enough of all that. It is equivalent, in a way, to Elis Regina’s “el todo,” at the end of some live versions of “Águas de Março.” It’s like all or nothing at all, each the other’s ally or double or deconstruction in the refusal of the (every)thing. This brings us to Myrta Silva. This brings us, with Licia, to the great woman singer’s discomposing embellishment of (male) composition, as in what Betty Carter does to Neal Hefti or Cole Porter; what Lucecita does to Guillermo Venegas Lloveras; what Myrta does to Rafael Hernández; what Elis does to Tom Jobim. Licia amplifies Myrta’s long-running making of much ado about nothing—and it runs not just through psychoanalytic and semiotic protocols of disavowal and (de)signification but against the grain, by way of but also in excess of Kaja Silverman and Shoshona Felman, showing how this making of something out of nothing always tends to undermine the seduction of meaning within phallic economies and the reduction of non-meaning in psychoanalytic interpretation. In other words, Licia hips us to how Myrta brings off—in getting the nation off, or in getting off the nation—the seduction that non-meaning bears in/as sound and gesture, rhythm and glance, in what J. L. Austin calls “mere accompaniments of the utterance.” Jack Halberstam says, the diva is she who transcends the norms of performance. We might also say: she is she who discomposes; or, she’s who mobilizes nonperformance. The voice as a thinking object. Thinking is Myrta working that low register, alongside Big Maybelle, say, or, in another way, Sarah Vaughan. What’s cool is just the way Myrta says “Nada.” She uses her whole face. Or, there is a mutual discomposition of face and voice in defiance of portraiture. What’s cool is the production of a sound and a persona—through and against voice and face or, at least, their reduction to (national or personal) identity. “Personare,” as Damien-Adia Morassa would say, with regard to Machado de Assis, but, somehow impersonal, or more + less than personal. Radical impersonation, radical ante-nationality, a hyperreality to which Myrta ought not be reduced but which she seduced into a non-normative, non-desertified fecundity, as the queer, more + less than rational productivity that marks the un(der)development of the nation. Licia teaches us how to want nothing but that!